TEAMWORK AND CAREER DEVELOPMENT WORK INVOLVEMENT WITH SELF DEVELOPMENT AS MEDIATING VARIABLE AT ABC COMPANY - Yohana Cahya Palupi Meilani; Oki Hermawati (Feedforward: Journal of Human Resource, 2023)
This research was conducted with the aim to determine the effect of Teamwork and Career Development on Self-Development and Employee Work Involvement of PT ABC employees. This research is a quantitative research with descriptive method. Sampling used a non-probability sampling technique, namely purposive sampling, where the respondents used were 135 permanent employees of PT ABC who worked in the Jakarta and Tangerang areas who had worked for more than 1 year. The data collection technique used a research instrument in the form of a questionnaire with a Likert scale of 1–5. The analysis technique is Structural Equation Model (SEM) using SmartPLS 3 software. Based on the results of the data analysis conducted, it can be concluded that teamwork has a positive and significant effect on employee self-development (H1), career development has a positive impact on employee self-development (H2), teamwork has a negative effect on employee job involvement (H3), career development has a positive effect on employee job involvement (H4), self-development has a positive effect on employee job involvement (H5), self-development is able to mediate the effect of teamwork on employee job involvement (H6), and self-development is able to mediate the effect of career development on employee job involvement (H7).Bahasa Indonesia Abstrak: Penelitian bertujuan untuk mengetahui pengaruh kerjasama tim dan pengembangan karier terhadap pengembangan diri dan keterlibatan kerja karyawan Perusahaan ABC. Penelitian ini merupakan penelitian kuantitatif dengan metode deskriptif. Pengambilan sampel menggunakan teknik nonprobability sampling yaitu dengan purposive sampling, di mana responden yang digunakan merupakan 135 karyawan tetap PT ABC yang berlokasi kerja di wilayah Jakarta dan Tangerang dengan masa kerja lebih dari satu tahun. Teknik  pengumpulan data menggunakan instrumen penelitian berupa kuesioner dengan skala Likert 1–5. Teknik analisis yaitu Structural Equation Model (SEM) dengan menggunakan software SmartPLS 3. Hasil penelitian ini menunjukkan bahwa kerjasama tim berpengaruh positif terhadap pengembangan diri karyawan (H1), pengembangan karier berpengaruh positif terhadap pengembangan diri karyawan (H2), kerja sama tim berpengaruh negatif terhadap keterlibatan kerja karyawan (H3), pengembangan karier berpengaruh positif keterlibatan kerja karyawan (H4), pengembangan diri berpengaruh positif terhadap keterlibatan kerja karyawan (H5), pengembangan diri mampu memediasi pengaruh kerja sama tim karier terhadap keterlibatan kerja karyawan (H6), dan pengembangan diri mampu memediasi pengaruh pengembangan karier terhadap keterlibatan kerja karyawan (H7).